Estudio técnico económico para la instalación de una planta de ladrillos en el Valle de Jequetepeque nivel pre-factibilidad - Zanini Delgado, Ixi Raquel (2018)
The present research work contains information on the technical economic study for the installation of a plant of three types of bricks in the Jequetepeque valley: Hueco 12, King Kong 18 and Tambourine 12. The study is based on the existence of a dissatisfied market since the wide variety and quality of bricks in the Jequetepeque Valley is not available. A survey was carried out based on the non-probabilistic sampling for convenience applied to two samples: Contractors and Companies Subcontractors of bricks. The methodology used was descriptive empirical since it seeks to specify the properties, characteristics and important features of the phenomenon that is being analyzed. The techniques of information collection were surveys, bibliographic review, statistics of the first indicators of the sector and direct observation. Likewise, the processing techniques were documentary and virtual review and review of previous results. To carry out the technical study, the following variables were used: commercial, technical, administrative and economic feasibility with their indicators: project demand, installed capacity, number of profiles required, VANE, TIRE, VANF, TIRF respectively. The study carried out with respect to the variables, projected a volume of production for the year 2017 of 943225 of bricks with a percentage of participation in the market of 20% for the year 2017, 30% for 2018, 40% for 2019, 50% for 2020 and 55% for the year 2021. The sale price was obtained for the three types of bricks: for the brick Pandereta 12 is $ 0.16, for the King Kong 18 brick is $ 0.20 and for the Hollow brick 12 is $ 0.71. The economic variables of the project show us profitability, since we have a VANE of $ 581,990, TIRE of 51.09%, Economic Cost Benefit Ratio of 1.3, VANF of $ 603,740, ITR of 57.30% and a Financial Cost Benefit Ratio of 1.19. In addition, the sensitivity analysis was carried out, which considers the following variables: income levels, production costs, administrative expenses, general expenses, sales expenses, fixed investment and working capital investment. With the help of the Crystal Ball software, which considers 1000 possible scenarios and simulates the results that the VAN and the IRR can assume through the random assignment of values for each relevant variable of the cash flow, thus showing a high probability of obtaining indicators of Attractive profitability for the period of study of the project.